2013
DOI: 10.1088/0004-6256/146/5/134
|View full text |Cite
|
Sign up to set email alerts
|

The Radial Velocity Experiment (Rave): Fourth Data Release

Abstract: We present the stellar atmospheric parameters (effective temperature, surface gravity, overall metallicity), radial velocities, individual abundances and distances determined for 425 561 stars, which constitute the fourth public data release of the RAdial Velocity Experiment (RAVE). The stellar atmospheric parameters are computed using a new pipeline, based on the algorithms of MATISSE and DEGAS. The spectral degeneracies and the 2MASS photometric information are now better taken into consideration, improving … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
314
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 300 publications
(330 citation statements)
references
References 91 publications
12
314
4
Order By: Relevance
“…It is important to note that the low end of the 90 per cent confidence interval, 2.5 × 10 11 M , is likely ruled out by observations of the inner part of the Galactic halo. Using the fourth data release of the Radial Velocity Experiment (Kordopatis et al 2013), Piffl et al (2014) found that the MW halo mass within 180 kpc is ≥9 × 10 11 M at 90 per cent confidence (Smith et al 2007;Xue et al 2008;Gnedin et al 2010;Deason et al 2012, found similar lower bounds, albeit with larger uncertainties). This result could, in principle, be used as a prior for the kind of analysis we have carried out in this paper, along with other constraints coming from the orbital properties of the massive satellites (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to note that the low end of the 90 per cent confidence interval, 2.5 × 10 11 M , is likely ruled out by observations of the inner part of the Galactic halo. Using the fourth data release of the Radial Velocity Experiment (Kordopatis et al 2013), Piffl et al (2014) found that the MW halo mass within 180 kpc is ≥9 × 10 11 M at 90 per cent confidence (Smith et al 2007;Xue et al 2008;Gnedin et al 2010;Deason et al 2012, found similar lower bounds, albeit with larger uncertainties). This result could, in principle, be used as a prior for the kind of analysis we have carried out in this paper, along with other constraints coming from the orbital properties of the massive satellites (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Gaia has already produced billions of RVS spectra and by the end of the mission, each star will be observed on average 40 times. This can be compared with the extremely successful RAVE survey (Radial VElocity Experiment, Kordopatis et al 2013), which measured RVs for half a million stars with V<12 mag. The Gaia end-of-mission errors will vary with the star's colour and will be of the order of 1 km s −1 for the bright red stars (G<12.5 mag and cooler than F types) and will be about 15-20 km s −1 or more for fainter and bluer stars.…”
Section: Radial Velocitiesmentioning
confidence: 99%
“…Despite the saturation, we were able to measure a parallax from the multiepoch VVV data: 40.35±7.19 mas and 49.07±7.06 mas (24.78 +5.4 −3.7 pc and 20.4 +3.4 −2.6 pc) respectively. 2MASS J20044356-7123334 (or LTT 7914) was observed by the RAdial Velocity Experiment (RAVE) in its fourth data release Kordopatis et al (2013) and described there. They derived a T ef f =4817 and log g=4 and metallicity [Fe/H]=0.05, based on this we could assume the dwarf nature and apply the relations described before, deriving a distance of 108 pc.…”
Section: Probable Multiple Systemsmentioning
confidence: 99%